STRATEGI INTERNATIONAL FUND FOR ANIMAL WELFARE (IFAW) DALAM MENGATASI PERBURUAN PAUS KOMERSIL DI ISLANDIA - Setyawan, Irwan (2022)
This paper discusses the efforts of the NGO International Fund for Animal Welfare (IFAW) which focuses on stopping commercial whaling in Iceland, which is one of 3 whaling countries for commercial purposes that are still actively searching for commercial whales. Commercial pause hunting is an illegal activity throughout the world, and has been regulated by many international treaties, one of which is the International Whaling Commission (IWC) Commercial Pause Hunting Moratorium in 1986, using descriptive research. As a result of efforts to stop Icelandic whaling, IFAW formed a campaign project in collaboration with the NGO "Meet Us Don't Eat Us" which aims to provide information about whaling in Iceland and promote holiday break tourism. Icelandic pause consumption then decreased and sighting tourism increased, the Icelandic government eventually expanded the pause sanctuary area, this policy made observing more opportunities, and the Icelandic Ministry of Fisheries will stop hunting commercial whales because it is no longer hunting for the economic impact on Iceland and now there's only 1 search company left, a gap that hasn't even searched since 2018.